The Association Between Maternal Knowledge of Immunization and Acceptance of Multiple Injection Immunization at Community Health Posts in an Urban Primary Healthcare Setting - Sabrina, Haifa Rafiqa; Husada, Dominicus; Ningtyas, Woro Setia; Lestari, Pudji (Rifa'Institute, 2026)
Introduction: Multiple injection immunization is a service strategy that administers more than one vaccine in a single visit to improve immunization efficiency and coverage. Despite evidence of safety, parental concerns regarding adverse effects remain a major barrier to its acceptance. Maternal knowledge plays a critical role in decision-making related to childhood immunization. Objective: This study aimed to analyze the association between maternal knowledge of immunization and acceptance of multiple injection immunization at community health posts in an urban primary healthcare setting. Method: An analytical observational study with a cross-sectional design was conducted among 82 mothers with children aged 2–24 months, selected using purposive sampling. Data were collected using structured questionnaires and analyzed using the Chi-square test. Result and Discussion: More than half of respondents demonstrated a high level of immunization knowledge (57.3%), and the majority accepted multiple injection immunization (68.3%). Among mothers who accepted multiple injections, 67.9% had a high knowledge level. Statistical analysis showed a significant association between maternal knowledge level and acceptance of multiple injection immunization (p = 0.001). Conclusions: Maternal knowledge of immunization is significantly associated with acceptance of multiple injection immunization. Strengthening educational interventions targeting mothers and families is essential to improve acceptance and sustain optimal immunization coverage.